Three new species of crab spiders (Araneae: Thomisidae) from Qizimeishan National Nature Reserve, China - Chen, Hailun; Liu, Jie; Hu, Changhao (Zootaxa, 2025)
Three new species of the family Thomisidae Sundevall, 1833 are described based on specimens collected from Qizimeishan National Nature Reserve, Hubei Province, China: Diaea erji sp. nov. (♀), Lysiteles tanfei sp. nov. (♂♀), and Tmarus ungulatus sp. nov. (♂♀). Diagnoses, descriptions, photos and a distribution map of the three new species are provided.